Line Spread Test Results for Commercially Available the White Rice Porridge with Salted Plum - Including the Effect of Four Types of Thickening Agents Added after Blending (Global Journal of Medical Research, 2023)
We added four commercially available thickeners to white rice porridge with salty plum which is popular in Japan and compared the viscosity Porridge containing water is useful even in the event of a disaster In Japan porridge is useful as a stockpile of food during disasters Porridge is used as a meal of a wide range of age groups form the elderly to infants However if porridge is made into a liquid using a mixer etc it becomes a food with a high risk of aspiration for people with impaired swallowing function Therefore it is necessary to add a thickener to the liquid porridge to increase its viscosity In order to keep the consistency the thickening agent should be changed according to the amount of nutrients contained in the porridge
Keywords: commercial product; white rice porridge with salted plum; lin spread test (LST); thickener